2005
DOI: 10.1159/000083707
|View full text |Cite
|
Sign up to set email alerts
|

Reservoir Function of the Stratum corneum: Development of an in vivo Method to Quantitatively Determine the Stratum corneum Reservoir for Topically Applied Substances

Abstract: Investigations on the stratum corneum (SC) reservoir for topically applied substances are of importance in dermatologic science in order to assess the pharmacokinetics of these substances. In the present study, an in vivo method was developed to determine the SC reservoir quantitatively and to investigate the temporal behavior of this reservoir. Therefore, increasing amounts of an oil-in-water emulsion (o/w emulsion) containing 4% of a chemical UV filter were topically applied onto the flexor forearms of 5 hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 37 publications
5
34
0
Order By: Relevance
“…In our work, considering the overall data ( table 1 ), a good in vitro/in vivo correlation was found. In the in vivo study the tape stripping methodology appears as a minimally invasive but powerful approach in obtaining information on the SC reservoir in real conditions [23] . However, the differences revealed in the SC distribution analyses suggest the need for parallel in vitro and in vivo experiments.…”
Section: Discussionmentioning
confidence: 99%
“…In our work, considering the overall data ( table 1 ), a good in vitro/in vivo correlation was found. In the in vivo study the tape stripping methodology appears as a minimally invasive but powerful approach in obtaining information on the SC reservoir in real conditions [23] . However, the differences revealed in the SC distribution analyses suggest the need for parallel in vitro and in vivo experiments.…”
Section: Discussionmentioning
confidence: 99%
“…31,32) Investigations with primaquine demonstrated that both binding to corneocyte keratin as well as the miscibility of the drug with the lipid domains contribute to the horny layer reservoir. 33) Furthermore, a higher amount of GEN retained in the skin could be advantageous to ensure continuous drug levels in skin tissues and/or to reduce frequent administrations. 31) CONCLUSION A simple HPLC bioanalytical method was developed and validated for the precise and accurate determination of genistein in different skin layers, applicable to skin permeation studies.…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of the chemical UV fi lter 4-methylbenzylidene camphor on the tape strips was analyzed spectroscopically using the modifi ed UV/VIS spectrometer for the determination of the UV absorption [31] .…”
Section: Determination Of the Uv Filter On Each Tape Strip (Study Desmentioning
confidence: 99%
“…The lengths of the bars in the penetration profi le correspond to the concentration of the UV fi lters in the corresponding depth of the SC. Therefore, the penetration profi le can be seen as a cut through the SC [31] .…”
Section: Calculation Of the Penetration Profi Les (Study Designs A Anmentioning
confidence: 99%